2020
DOI: 10.1155/2020/5354825
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Prognostic Characteristics of CD276 (B7-H3) Expression in Adrenocortical Carcinoma

Abstract: Background. Adrenocortical carcinoma (ACC) is a rare malignant endocrine tumor with a high tumor recurrence rate and poor postoperative survival. Recent studies suggest that CD276- (B7-H3) targeted therapy represents a promising therapeutic option for solid tumors. However, little is known about the expression status of CD276 or its association with progression and prognosis of ACC. Methods. Clinical data were retrospectively analyzed from patients who underwent resection of ACC at our institution (n=48). Arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In agreement with recent findings showing that 90% of ACC samples (n = 48) were positive for B7-H3 ( CD276 ) in immunohistochemical assays ( 60 )⁠, our analysis demonstrated that CD276 overexpression was detected in both LSP and HSP. Remarkably, its expression was considered high in a pan-cancer comparison of most ACC patients ( Figure 7B ).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with recent findings showing that 90% of ACC samples (n = 48) were positive for B7-H3 ( CD276 ) in immunohistochemical assays ( 60 )⁠, our analysis demonstrated that CD276 overexpression was detected in both LSP and HSP. Remarkably, its expression was considered high in a pan-cancer comparison of most ACC patients ( Figure 7B ).…”
Section: Discussionsupporting
confidence: 93%
“…Cytoplasmic CD276 expression is negatively correlated with both the overall survival and disease-free survival of ACC patients. Gene set enrichment analysis demonstrated that CD276 expression is closely related to immune regulation and malignant biological behavior of ACC (24). To give a more intuitive aspect of the expression level of CD276 in malignancies, we performed a pan-cancer analysis to evaluate CD276 expression level in multiple cancers on UALCAN database (http://ualcan.path.uab.edu/index.html).…”
Section: Expression and Regulation Of Cd276 In Tumor Expression Levelmentioning
confidence: 99%
“…Cytoplasmic CD276 expression is negatively correlated with both the overall survival and disease-free survival of ACC patients. Gene set enrichment analysis demonstrated that CD276 expression is closely related to immune regulation and malignant biological behavior of ACC ( 24 ).…”
Section: Expression and Regulation Of Cd276 In Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that >90% of the samples expressed CD276, and more than half of the samples showed moderate to strong expression. Furthermore, higher intensity of CD276 in tumor cells correlated with increased recurrence risk and overall worse prognosis, while at the same time, increased expression of CD276 in tumor vasculature was associated with tumor invasion of adjacent structures and more advanced disease stage [ 36 ].…”
Section: Tumor Immune Microenvironment In Adrenocortical Carcinomamentioning
confidence: 99%